Hsa-miR-155-5p Up-Regulation in Breast Cancer and Its Relevance for Treatment With Poly[ADP-Ribose] Polymerase 1 (PARP-1) Inhibitors - Pasculli, Barbara; Barbano, Raffaela; Fontana, Andrea; Biagini, Tommaso; Di Viesti, Maria Pia; Rendina, Michelina; Valori, Vanna Maria; Morritti, Maria; Bravaccini, Sara; Ravaioli, Sara; Maiello, Evaristo; Graziano, Paolo; et al. (Frontiers in Oncology, 2020)
miR-155-5p is a well-known oncogenic microRNA, showing frequent overexpression in human malignancies, including breast cancer. Here, we show that high miR-155-5p levels are associated with unfavorable prognostic factors in two independent breast cancer cohorts (CSS cohort, n=283; and TCGA-BC dataset, n=1095). Consistently, miR-155-5p results as differentially expressed in the breast cancer subgroups identified by the surrogate molecular classification in the CSS-cohort and the PAM50 classifier in TCGA-BC dataset, with the TNBC and HER2-amplified tumors carrying the highest levels. Since the analysis of TCGA-BC dataset also demonstrated a significant association between miR-155-5p levels and the presence of mutations in Homologous Recombination (HR) genes, we hypothesized that miR-155-5p might affect cell response to the PARP-1 inhibitor Olaparib. As expected, miR-155-5p ectopic overexpression followed by Olaparib administration resulted in a greater reduction of cell viability as compared to Olaparib administration alone, suggesting that miR-155-5p might induce a synthetic lethal effect in cancer cells when coupled with PARP-1-inhibition. Overall, our data point to a role of miR-155-5p in Homologous Recombination Deficiency and suggest miR-155-5p might be useful in predicting response to PARP1 inhibitors in the clinical setting.